Synthesis, characterization and investigation of electrical and electrochemical properties of imidazole substituted phthalocyanines - Yabas, Ebru; Sulu, Mustafa; Saydam, Sinan; Dumludag, Fatih; Salih, Bekir; Bekaroglu, Ozer (Elsevier Science Sa, 2011)
Compound 1 has been synthesized by the reaction of 4-nitrophthalonitrile and 4,5-diphenyl-1H-imidazolethiole in DMSO in the presence of K2CO3. Compound 2 has been synthesized by heating compound 1 with metallic lithium in pentanol and hydrolyzed with hydrochloric acid (10%) and then neutralized with ammonia solution. Compound 3 and 4 have been synthesized by heating 1 with ZnCl2 or CoCl2 in DMF in the presence of 1,8-diazabicyclo[5.4.0] undec-7-ene (DBU), respectively. The new compounds were obtained in sufficient purity after successive washing with different solvents and were characterized by elemental analysis, H-1 NMR, C-13 NMR, UV-vis, IR and mass spectra. We also studied aggregation behavior, electrochemical and electrical properties of these phthalocyanines. Direct current (dc) and alternating current (ac) conductivity (40-100 kHz) measurements of films of 2, 3 and 4 were performed in the temperature range of 295-523 K. Impedance spectra (IS) of the 2, 3 and 4 were also studied. The conduction processes were discussed. Temperature dependence of dc conductivity of the films revealed that 2, 3 and 4 show a semiconductor behavior. Results of ac measurements showed that, conduction processes of the films of the complex consisted of different mechanisms depending on temperature and frequency. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Imidazole; Phthalocyanines; Metal complexes; Aggregation; Electrical properties; Electrochemistry